Predictor Analysis in Radiofrequency Ablation of Benign Thyroid Nodules: A Single Center Experience - Bisceglia, Alessandro; Rossetto, Ruth; Garberoglio, Sara; Franzin, Angelica; Cerato, Alice; Maletta, Francesca; Papotti, Mauro Giulio; Ghigo, Ezio; Pagano, Loredana; Maccario, Mauro; Garberoglio, Roberto (Frontiers in Endocrinology, 2021)
Purpose: To confirm the efficacy of ultrasound (US) guided radiofrequency ablation (RFA) in treatment of benign thyroid nodules, we evaluated as primary outcome the technical efficacy and clinical success in a single center dataset. The secondary outcome was to find a correlation between nodules’ pre-treatment features and volume reduction rate (VRR)  75% at 12 months after RFA and during follow-up period. Methods: This retrospective study included 119 consecutive patients (99 females, 20 males, 51.514.4 years) with benign thyroid nodules treated in our hospital between October 2014 and December 2018 with a mean follow-up of 26.8 months (range 3 - 48). Clinical and US features before and after RFA were evaluated by a US examination at 1, 3, 6, 12 months and annually thereafter up to 48 months. Results: The median pre-treatment volume was 22.4 mL; after RFA we observed a statistically significant volume reduction from the first month (11.7 ml) to the last follow-up (p < 0.001 for all follow-up times). The median VRR was 47.1%, 55.3%, 61.2%, 67.6%, 72.8%, 71.3%, 62.9% at 1-3-6-12-24-36-48 months of follow-up respectively, showing a progressive significant improvement up to 24 months (VRRs 1 vs 3 months, 3 vs 6 months and 6 vs 12 months p < 0.001, 12 vs 24 months p = 0.05) while no differences at 24 vs 36 and 36 vs 48 months were observed. Symptoms improved significantly (complete resolution 64.35%, partial resolution 35.65%) and neck circumference was reduced as compared to pre-treatment (p < 0.001). Lower pre-treatment neck circumference (37.5 vs 36.0 cm, p = 0.01) was a positive predictor of VRR 75% at 12 months. Macrocystic echostructure (HR 2.48, p 0.046) and pre-treatment volume >22.4 mL (HR 0.54, p 0.036) were found independent positive and negative predictors of VRR 75% respectively. One-month post RFA VRR 50% represented the best positive predictor of technical success. Conclusions: This study confirmed the efficacy of RFA in treatment of benign thyroid nodules. In particular we show that by selecting macrocystic nodules smaller than 22.4 mL better long-term response can be achieved, which is predicted by an early shrinkage of the nodule.